Transcervical resection of endometrium in women with menorrhagia. - Magos, A. L. (1989)
As an alternative to hysterectomy 16 women with menorrhagia were treated with hysteroscopic transcervical resection of the endometrium with an unmodified urological resectoscope. Twelve patients requested total resection of the endometrial lining with the intention of producing amenorrhoea, and four chose partial resection and hypomenorrhoea. Surgery was completed successfully in 15; the remaining woman, who had an acutely retroflexed uterus, sustained a uterine perforation during insertion of the rigid hysteroscope. There were no important postoperative complications, and 13 patients were discharged from hospital the day after operation. Follow up for up to six months showed beneficial effects on the duration of menses and the subjective assessment of menstrual blood loss and pain in the treated women, six of them becoming amenorrhoeic after total resection. Hysteroscopy at three months in 13 patients showed fibrosis confined to the upper half of the uterine cavity. Endouterine biopsy specimens showed the presence of microscopic deposits of normal endometrium in 10 women. Although these results are preliminary, transcervical resection of the endometrium may have an important role in managing this common complaint.